Rebel Girls : Youth Activism and Social Change Across the Americas. - Taft, Jessica K. (NYU Press, 2010)
From anti-war walkouts to anarchist youth newspapers, rallies against educational privatization, and workshops on fair trade, teenage girls are active participants and leaders in a variety of social movements. Rebel Girls: Youth Activism and Social Change Across the Americas illuminates the experiences and perspectives of these uniquely positioned agents of social change. Jessica K. Taft introduces readers to a diverse and vibrant transnational community of teenage girl activists in the San Francisco Bay Area, Mexico City, Caracas, Buenos Aires, and Vancouver. Expansive in scope and full of ri.